Overview of Adolescents' Perceptions of Bullying - Hasna Rahel; Rasmita, Dina; Suza, Dewi Elizadiani; Ariadni, Dwi Karina (Universitas Prima Indonesia, 2025)
Bullying behavior continues to increase from year to year, one of which occurs among Indonesian students. Most bullying behavior is found at the senior high school level. Adolescent perceptions of bullying play an important role in efforts to prevent and handle this problem. The purpose of this study was to determine the description of students' perceptions towards bullying behaviour that they do at school. The type of research used is quantitative research with a descriptive design involving 73 students using probability sampling techniques with the type of systematic sampling. Data were collected through questionnaires and processed with descriptive statistics. The results showed that the majority of adolescents had good perceptions of bullying, namely 62 respondents (84.9%), and sufficient perceptions, as many as 11 respondents (15.1%). The majority of respondents have good perceptions, so that adolescents are expected to maintain and increase their understanding that bullying is an action that is not commendable, so that the prevention of bullying can increase.